Anidamientoydieta de Harpia harpyja Linnaeus en la Comunidad Nativa de Infierno, Madre de Dios, Perú - Piana, Renzo P. (2007)
The Harpy Eagle (Harpia harpyja Linnaeus) is the biggest raptor that inhabits the Amazonian rainforest, however, in Perú, little is known about the biology of the species. Since 1996 to 2001, a research on the nesting characteristics and diet of the Harpy Eagle was conducted in the Native Community of Infi erno, through the localization and observation of active and abandoned nests. This research has found the fi rst active nests reported for H. harpyja in Peru and its probable preference to nest in Brazil nut trees stands. The data collected showed that the nesting area for a couple of eagles in the study area is of approximately 4300 hectares. The analysis of prey remains and casts collected inside and under the nests allowed the fi rst description of the diet H. harpyja, which is mainly composed of arboreal mammals.